Effects of different spacings on the allometric growth of rubber nursery seedlings - Cid, Luis Pedro Barrueto; Rossetti, Adroaldo Guimarães (Pesquisa Agropecuaria Brasileira, 2014)
In a rubber nursery study seven spacings were evaluated, comparing increase in stem height and stem diameter measured at 5 cm from the soil, on seedlings derived from seeds of native rubber trees (Hevea spp.). No statistical difference was found among the allometric constants (Id used to compare the spacings. In all cases, the k values were superior than 1.0 showing the greater tendency to increase in stem height rather than in diameter. Although the stem growth in diameter was observed in all the leaf phenological stages, they were more evident in stages B and D of the canopy development. For the selection of a nursery spacing, economical considerations of cost/benefit and field practices are therefore more important factors to be taken into account than growth alone.
Keywords: stem diameter; seeds; phenological state